Mathematical Model for Perforation Effect on Modified Atmosphere Packaging of Shelled Pea - Sharma, Sajeev Rattan; Chand, Tarsem (Journal of Agricultural Engineering, 2010)
A mathematical model was developed for shelled pea packaged in simulated modified atmosphere packages of LD- 100 (low density polyethylene of 100 gauge, 25 micron thick, to evaluate the effect of perforation level on the concentrations of O2 and CO2 and levels of relative humidity inside the package. Experiments were carried out to verify the model results. Perforations resulted in reducing the steady state times of O2 and CO2, and the effect was more pronounced on O2. The increase in number of perforations and decrease in ambient relative humidity predicted a little decrease in relative humidity within the package but it remained above 98 per cent. A perforation area of 6.51 x 10?Â² % was predicted to give optimum in-package environment for shelled pea.